1998
DOI: 10.1257/jep.12.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Students in U.S. Doctoral Programs

Abstract: In 1996, foreigners represented over half of the doctoral student population in economics, up from 20 percent in 1972. This article presents a profile of foreign students in economics Ph.D. programs in the United States based on survey and interview data collected in 1996. In addition to exploring students' assessment of their education, interests and career plans, the authors offer explanations for the rising proportion of foreign students, explore the implications of this phenomenon, and suggest the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…It is worth noting that foreign graduate students have a high propensity to remain in the United States, at least for the early proportion of their careers, and those who are educated in that country earn higher wages (Bratsberg and Ragan, forthcoming;Schoeni, 1997). Aslanbeigui and Montecinos (1998) On a negative note, Borjas (2002) speculates that foreign students in the United…”
Section: B Foreign Graduate Students and Skilled Immigrationmentioning
confidence: 99%
“…It is worth noting that foreign graduate students have a high propensity to remain in the United States, at least for the early proportion of their careers, and those who are educated in that country earn higher wages (Bratsberg and Ragan, forthcoming;Schoeni, 1997). Aslanbeigui and Montecinos (1998) On a negative note, Borjas (2002) speculates that foreign students in the United…”
Section: B Foreign Graduate Students and Skilled Immigrationmentioning
confidence: 99%
“…In addition to their economic contributions, international students bring racial and ethnic diversity to our campuses (Andrade 2006;Aslanbeigui and Montecinos 1998;Klomegah 2006;Lee and Rice 2007;Olivas and Li 2006), a benefit that often extends beyond their graduation as many of the international students who seek advanced research degrees become professors at US colleges or universities (Dreher and Poutvaara 2005). Furthermore, Stephan and Levin (2003) found that foreign-born scholars working in the science and engineering disciplines represent a disproportionately high percentage of those who make exceptional contributions to US industry.…”
mentioning
confidence: 99%
“…It has also inspired a lot of historical research on the internationalization or Americanization of economics, focusing on the postwar period. See, for instance, the contributions in Coats (1996aCoats ( , 2000, and Aslanbeigui and Montecinos (1998). 2 On the influence of German-speaking immigrants on American economics, see, e.g.…”
Section: Notesmentioning
confidence: 99%